H3K4me2 Promotes the Activation of lncCPSET1 by Jun in the Chicken PGC Formation - Chen Zhang; Qisheng Zuo; Xiaomin Gao; Cai Hu; Shujian Zhou; Chen Chen; Yichen Zou; Juanjuan Zhao; Yani Zhang; Bichun Li (Animals, 2021)
Primordial germ cells are the ancestors of female and male cells. Current research has shown that long non-coding RNA (lncRNA) and Histone methylation are the pivotal epigenetic factors in the PGC formation. However, there are few studies on the regulatory mechanism of lncRNA in the formation of PGC. Here, we define the lncRNA highly expressed in chicken PGC, lncCPSET1 (chicken-PGC-specifically-expressed transcript 1) This study found that compared with the interference of lncCPSET1/histone methylase Mll2 alone, the PGC formation was severely inhibited with the interference of lncCPSET1 and histone methylase Mll2 jointly in vivo and in vitro. Studies on the transcription level of lncCPSET1 found that H3K4me2 and transcription factor Jun have a positive effect on the activation of lncCPSET1; while DNA hypomethylation inhibits the expression of lncCPSET1. In terms of mechanism, compared with DNA methylation, H3K4me2 dominates lncCPSET1 activation. H3K4me2 can be enriched in the lncCPSET1 promoter, change its chromosome conformation, recruit the transcription factor Jun, and activate the expression of lncCPSET1. Taken together, we confirmed the model that H3K4me2 rather than DNA hypomethylation mediates Jun to regulate lncCPSET1 transcription, which broadens the study of lncCPSET1 pre-transcriptional mechanism.